Deciphering the anti-filarial potential of bioactive compounds from Ocimum sanctum: a combined experimental and computational study. (31st December 2022) - Mishra, Ayushi; Kumar, Vipin; Singh, Anchal
Abstract: Context: The anthelminthic effect of Ocimum species (Lamiaceae) has been reported, however, its anti-filarial effect has not been explored to date. Objective: This study evaluates the effect of Ocimum sanctum L. (OS) against lymphatic filarial parasites. Material and methods: The ethanol extract of OS (EOS) leaves was tested for anti-filarial activity against Setaria cervi . Equal size and number ( n = 10) of adult female S. cervi worms were incubated in 125, 250 or 375 μg/mL EOS extract for 6 h at 37 °C. The OS bioactive components were identified by UPLC-ESI-MS/MS and subjected to docking and molecular dynamics (MD) simulation against filarial antioxidant proteins. Results: The EOS significantly inhibited the motility of adult female S. cervi after 6 h of incubation. The motility was found to be reduced by 53.7% in 375 µg/mL and 43.8% in 250 µg/mL EOS after 6 h of treatment. The UPLC-ESI-MS/MS analysis of ethanol extract of O. sanctum revealed the presence of 13 bioactive compounds. The docking analysis showed eight OS bioactive compounds to have high binding affinity (> 4.8 kcal/mol) towards antioxidant proteins of filarial parasites. Additionally, MD simulation studies showed significant impact of (RMSD ≤ 10 Å) chlorogenic acid, luteolin and ursolic acid on filarial antioxidant enzymes/proteins. To our knowledge, this is the first report of the anti-filarial activity of Ocimum sanctum . Discussion and conclusions: The effect of EOS and OS bioactive components on human filarial parasites can be further evaluated for the development of new anti-filarial formulations.